Measurements of fluctuation in drag acting on rigid cylinder array in open channel flow - Zhao, Kuifeng (2014)
In this study, an array of rigid cylindrical rods was used to simulate emergent vegetation stems that were subject to unidirectional open channel flows. The instantaneous drag force experienced by the rods was measured with a load cell. In addition, the particle image velocimetry (PIV) technique was applied to sample the flow information in a horizontal plane, and wave gauges were used to record the fluctuation in the water-surface elevation. The results show that the drag fluctuation normalized by the mean value may reach as high as 133% when the Reynolds number (defined based on the stem diameter) varied in the range from 400 to 1,100. High fluctuations were also observed in the flow velocity and flow depth under similar flow conditions.